Productivity and quality of the grain of castor bean cultivated in the Central-North Mexico - Rosales-Serna , Rigoberto; Arellano-Arciniega, Sergio; Nava-Berumen, Cynthia Adriana; Santana-Espinoza, Saúl; Borja-Bravo, Mercedes; Ortiz-Sánchez, Ixchel Abby; Martínez-Reyes , Ernesto (Ecosistemas y Recursos Agropecuarios, 2023)
Raw materials are required to make biofuels and move towards sustainable sources of energy. The objective of the study was to evaluate the morphology, productivity and quality of the castor bean (Ricinus communis) grain cultivated in the Center-North of Mexico. In spring-summer 2020, four castor varieties and one hybrid were planted in Durango, Dgo., and Pabellón, Ags., México. In sowing, a density of 15,000 plants ha−1 was considered. Number of days to flowering (DF), plant height (AP), spike length (LE), yield (kg ha−1), weight of 100 seeds (P100S), % sprouting (PB), % germination (PG) and the ash (CC), protein (CP) and fat (CG) content. The statistical processing included descriptive statistics (DF, PB and PG) and an analysis of variance in a completely randomized block design with six repetitions and the comparison of means was obtained with the Tukey test (α ≤ 0.05). Highly significant differences (α ≤ 0.01) were observed for plant height between locations (195.0 cm-282.7 cm) and between materials for AP, LE and P100S. In both locations SAB 14 (2,906 kg ha−1 and 2,408 kg ha−1) and K 855 (2,669 kg ha−1 and 2,400 kg ha−1) showed the highest yield. In CG Guanajuato Oil (57.1%) and SAB 14 (55.4%) they statistically outperformed the rest of the materials. The adaptation of SAB 14 was confirmed, which showed high grain yield and its seeds were of acceptable quality, based on fat content.